RANCANG BANGUN SISTEM ALARM KONDISI SUHU PADA KANDANG REPTIL BERBASIS IOT - Ningsih, Setia; Ellbert Hutabri (LPPM Universitas Putera Batam, 2024)
The research proposes an IoT-based temperature alarm system addressing challenges in maintaining precise enclosure temperatures for reptile husbandry. The system, utilizing the DHT11 temperature sensor and Blynk platform, enables remote monitoring of reptile enclosures. When temperatures deviate from the desired range, the sensor transmits data to the system controller, which, in turn, sends warning notifications to users' smartphones. This prototype empowers users to make timely adjustments, such as deactivating UV lamps or activating fans, to maintain optimal enclosure temperatures. Ultimately, the system offers a practical solution for reptile caretakers, ensuring the well-being of reptiles by closely mimicking their native habitats through effective temperature control.